A Highly Contiguous Genome Assembly of Arthrinium puccinoides. (28th January 2022) - Sørensen, Trine; Petersen, Celine; Fechete, Lavinia I; Nielsen, Kåre L; Sondergaard, Teis E
Abstract: The phylogenetic relationship of the Arthrinium genus has changed throughout the years. For many years, the Arthrinium genus included the Apiospora genus as well. New evidence has now showed that these two genera in fact are phylogenetically different and belong to two different clades. Here, we present the first genome draft within the Arthrinium genus. This genome was sequenced using the MinION platform from Oxford Nanopore Technologies and the assembly was contiguous. The assembly comprises ten contigs totaling 39.8 Mb with an N50 length of 7.9. In the assembly, 11, 602 genes were predicted whereof 10, 784 were functionally annotated. A total of 37 rRNA genes were observed in the assembly and repeat elements spanning 7.39% of the genome were found. A total of 99 secondary metabolite gene clusters were predicted, showing a high potential of novel secondary metabolites. This genome sequence will not only be useful for further investigation of the Arthrinium clade, but also for discovery of novel secondary metabolite compounds that could be of high interest for the food, agricultural, or pharmaceutical industry.